The Screwtape letters - Lewis, C. S. (Clive Staples), 1898-1963.; Lewis, C. S. (Clive Staples), 1898-1963 (Mattituck, N.Y. : American Reprint Co., 1980)
C. S. Lewis's mockery of the Devil, which presents advisory letters from a demon to his young nephew explaining how to tempt a man away from God. Includes Lewis's 1960 preface, as well as his criticism of American education, "Screwtape Proposes a Toast."
CONTENTS: Screwtape proposes a toast.
Includes Screwtape proposes a toast.
Keywords: Christianity -- 20th century